Case studies in Physiology (St. Louis, Missouri, 1994)
The book deals with various important physiologic concepts and principles by the questions and answers. It illustrates physiology constitutes the basis of madicine, and indicates how medicine is essentially abnormal physiology. All of the questions raised about each case are answered in the back of the book, some in great detail. In addition, references are cited to appropriate pages in the book foe a consideration of the physiologic mechamisms that realte to the question posed
Keywords: human physiology - problems, exercises, etc,physioloy - problems, exercises, etc